MODELLING TEACHING VOCABULARY MASTERY BY GAME- BASED LEARNING APPROACH - Ida Royani; Sojuangon Rambe; Nurun Najiah; Khoirunnisa Khoirunnisa; Sopiah Nuriani Siagian; Bunga Rizky Nauli Rangkuti (Esteem Journal of English Education Study Programme, 2026)
This study investigates the effectiveness of game-based learning strategies in enhancing the vocabulary proficiency of eighth-grade junior high school students. Specifically, it examines and compares the impact of the Word Chain Game, Mnemonic Technique, and Jumble Word Game on students’ vocabulary acquisition and retention. A quantitative methodology was employed, utilizing experimental and quasi-experimental designs across three junior high schools. Participants were selected through random sampling in three separate studies. The Word Chain Game study involved 61 students, the Mnemonic Technique study included 56 students, and the Jumble Word Game study consisted of 60 students, each divided into experimental and control groups. Data were gathered through multiple-choice pre-tests and post-tests and analyzed using t-tests with SPSS software. The findings revealed that all three instructional approaches significantly improved students’ vocabulary mastery. The Word Chain Game demonstrated the strongest effect (t = 6.463), followed by the Mnemonic Technique (t = 5.667) and the Jumble Word Game (t = 3.020). These results indicate that game-based learning promotes greater engagement and strengthens vocabulary retention. The novelty of this study lies in its integrative analysis of three distinct vocabulary-learning interventions, providing comprehensive evidence that interactive and game-oriented strategies effectively support vocabulary development among junior high school learners.